Standardized spider (Arachnida, Araneae) inventory of Hankoniemi, Finland - Cardoso, Pedro (Biodivers Data J, 2017)
Abstract. BACKGROUND: During a field course on spider taxonomy and ecology at the University of Helsinki, the authors had the opportunity to sample four plots with a dual objective of both teaching on field methods, spider identification and behaviour and uncovering the spider diversity patterns found in the southern coastal forests of Hankoniemi, Finland. As an ultimate goal, this field course intended to contribute to a global project that intends to uncover spider diversity patterns worldwide. With that purpose, a set of standardised methods and procedures was followed that allow the comparability of obtained data with numerous other projects being conducted across all continents. NEW INFORMATION: A total of 104 species and 1997 adults was collected. Of these, 41 species (39%) were Linyphiidae and 13 (12%) Theridiidae. All other families had 6 or less species represented. Linyphiidae were also dominant in terms of adult individuals captured, with 1015 (51%), followed by 428 (21%) Lycosidae, 158 (8%) Tetragnathidae and 145 (7%) Theridiidae. All other families had less than 100 individuals. The most abundant species were Neriene peltata, Alopecosa taeniata, Piratula hygrophila and Dismodicus elevatus, all with more than 100 individuals. All sites had between 56 and 62 species and between 445 and 569 individuals.